2010
DOI: 10.1001/archpediatrics.2010.216
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-term Risk of Infections as a Function of Group Child Care Attendance

Abstract: To determine whether the frequency of infections during the first 8 years of life varies according to age at initiation and type of group child care (GCC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 12 publications
4
30
2
2
Order By: Relevance
“…7,15,16,24 Depending on age at entry, the increase in AGE incidence among daycare attendees was observed in our study during the first or first and second year only. The seasonal peak during winter months suggests an important contribution of rotavirus and norovirus to the increased AGE incidence for first-year daycare attendees.…”
Section: Figurementioning
confidence: 51%
See 2 more Smart Citations
“…7,15,16,24 Depending on age at entry, the increase in AGE incidence among daycare attendees was observed in our study during the first or first and second year only. The seasonal peak during winter months suggests an important contribution of rotavirus and norovirus to the increased AGE incidence for first-year daycare attendees.…”
Section: Figurementioning
confidence: 51%
“…Our findings are in line with results from 2 other prospective cohort studies that assessed direct and long-term effects of early daycare on AGE occurrence. Côté et al 15 did not find a difference in cumulative parentreported AGE incidence in the first 8 years of life between children attending daycare before ages 2.5 years and those not attending daycare. Zutavern et al 8 found an increased risk, based on parental questionnaires, of several infections, including AGE, in the first years of life for children who entered daycare before 2 years of age, and observed that this risk disappeared or even reversed from the age of 4 years on.…”
Section: Figurementioning
confidence: 88%
See 1 more Smart Citation
“…For the 0-2 year-olds parent-reported measures such as "never had a nose/throat/ear infection" are used. These are benign health outcomes and this life experience may have reinforce their immunitary system and their long term health (Ball et al 2002;Lu et al 2004;Côté et al 2010). For children aged 2 to 3 the behaviour of the child is measured using an emotional anxiety score, a physical aggression score, and a separation anxiety score, each based on a serie of parent-reported measures.…”
Section: Complement To Ecec and Child Development Literaturementioning
confidence: 99%
“…It is postulated that the risk is proportional to the number of "companions" the children are in contact with [5,6]. Large group child care centers increase otitis media incidence and were defined as those in which professional educators provided care for up to 10 groups of 8-12 children in the same setting [54]. A possible mechanism is related to the greater number of URTI presented by children that are exposed to many other children [55].…”
Section: Day-care Center Attendancementioning
confidence: 99%